Novagenesis control agent for future Internet eXchange point - Silva, Thiago Bueno (2021)
The Internet has become a public utility service and changed our leisure, work, and economy models. However, the current architecture and infrastructure of the Internet need mprovement to support future applications. Some limitations concern the support for the identification, mobility, and security of entities in the network. These and other drawbacks have driven the development of Future Internet Architectures, where some revolutionary projects rethink the Internet from scratch, e.g. NovaGenesis. When considering the current complexity and heterogeneity of technologies, a future requirement can arise in the form of a multi-architectural network, where disjoint architectures coexist in the same infrastructure to fulfill varied operational requirements. Therefore, Internet Exchange Points will be crucial to forward packets of different nature. This work presents the NovaGenesis Control Agent for Future Internet eXchange Point based on the P4 architecture. This dissertation proposal advances the state-of-the-art by developing a native and efficient controller for the NovaGenesis architecture that dynamically manages a Data Plane. The proposed prototype validates the bottom-up solution adopted in varied topologies without significantly affecting the content exchange evaluation scenario.